Edukasi Pemeriksaan Payudara Sendiri (SADARI) Sebagai Bentuk Deteksi Dini Kanker Payudara - Endah Tri Wahyuni; Nining Sulistyawati (ABDIMAS Madani, 2023)
ABSTRACT Breast cancer is a condition in which cells have lost their normal control and mechanisms, resulting in abnormal, rapid, and uncontrolled growth. One of the causes of this disease cannot be cured if it is found at an advanced stage. Surveys prove that cancer cases of breast cancer patients who come to health workers are already in a severe condition. According to the WHO report, breast cancer is the second leading cause of death after cervical cancer (cervical cancer). Breast cancer can be detected earlier by means of breast self-examination, clinical examination, and mammography examination to find out early. The purpose of this service is to increase knowledge and change behavior regarding early detection of breast cancer through Breast Self-examination (BSE) at the Al Ukhuwah Islamic Boarding School, Sukoharjo. The targets of this community service are students in grades 10-12. The number of subjects involved was 125 students. The implementation method of this community service activity is in the form of counseling related to a brief description of Ca Mamae and the direct practice of self-breast examination (BSE). The results of the pre-implementation evaluation showed that the majority of students lacked knowledge of 96 students (77.6%). As for the results of the post test evaluation, it was found that the majority had good knowledge of 120 students (96%) about breast self-examination.